Impact of Acacia mangium Willd. Plantation on Species Composition at Bugoy’s Peak, Barangay Bonbon, Butuan City, Philippines - Calope, Reymark Moring; Villa, Nathaniel Buron; Palas, Louie Jay Fijo; Corbita, Victor Lobrigas; Casilac Jr, Cornelio Sacquiap; Cossid, Rey Naldoza; Perodes, Mark Angelo Palero (Jurnal Sylva Lestari, 2025)
Acacia mangium is a fast-growing tree species widely used in agroforestry and reforestation. However, it has raised concerns due to its potential ecological impacts when introduced outside its native range. This study assessed the effect of A. mangium plantations on species composition and seedling recruitment at Bugoy’s Peak, Barangay Bonbon, Butuan City, Philippines. A total of 13 plots were established using a nested quadrat design to evaluate tree diversity and regeneration patterns. Biodiversity indices and statistical tools were employed to analyze species abundance and composition within the plantation area. Results indicated that A. mangium did not exhibit signs of invasive dominance in the site. On the contrary, the presence of regenerating native species across plots suggests that local conditions may support coexistence and recruitment despite the presence of an introduced species. These findings highlight the importance of site-specific assessments in evaluating the ecological impact of non-native tree species and offer valuable insights for sustainable plantation management in biodiverse landscapes. Keywords: Acacia mangium, diversity assessment, invasive species, seedling regeneration, species composition